THE DIFFICULTIES OF TEACHING ENGLISH TO ADULT LEARNERS IN THE MODERN WORLD. - Zulfizar Qo'chqorova Abduxamid qizi; Yulchiyeva Xulkaroy Dilmurod qizi (TADQIQOTLAR.UZ, 2023)
ABSTRACT Teaching English to adult learners in today's developing world comes with its own unique set of challenges. This article focuses on the difficulties faced by teachers in instructing English. It also discuss cognitive, attitudinal and behavioural characteristics which are presented by the adult learners.